Graphene synthesis and applications - Choi, Wonbong, 1963-; Lee, Jo-won, 1952- (Nanomaterials and their applications, 2012)
"Because of its exceptional electronic and optoelectronic properties, graphene has the potential to become an important material in next-generation electronic and energy applications. This authoritative volume discusses the synthesis, properties, and potential applications of graphene, including in electronic, sensor, energy, and display technologies. Suitable for researchers and graduate students, it provides a cohesive, critical review of graphene nanoscience and technology, offering valuable insight into how this material is made and used"--